Quality of life in long term survivors of pediatric intestinal transplantation compared with liver transplantation and home parenteral nutrition: A prospective single‐center pilot study. (16th February 2021) - Proli, Francesco; Metou‐Lopes, Adamadia; Ayachi, Amel; Rossi, Matilde; D'Arcangelo, Giulia; Faragalli, Andrea; Lambe, Cécile; Talbotec, Cécile; Goulet, Olivier; Chardot, Christophe; Lacaille, Florence
Abstract: Health‐related quality of life (HRQOL) after intestinal transplantation (IT) is important, as many psychological troubles have been reported in these patients on the long term. Our aim was to assess and compare HRQOL of patients after IT to patients after liver transplantation (LT) or on home parenteral nutrition (HPN) for intestinal failure. A cross‐sectional study included patients and their parents between 10 and 18 years of age, on HPN for more than 2 years, or who underwent IT or LT, with a graft survival longer than 2 years. Quality of life was explored by Child Health Questionnaire. Thirteen children‐parents dyads after IT, 10 after LT, and eight children on HPN completed the survey. Patients were a median age of 14 years old, a median of 10 years post‐transplantation or on HPN. Patients after IT scored lower than patients after LT or on HPN in "social limitations due to behavioral difficulties" and in "behavior." They scored higher than those on HPN in "global health." Parents of children after IT scored lower than those after LT in many domains. No relevant correlation with clinical data was found. Our study showed the multi‐level impact of IT on quality of life of patients and their parents. It highlights the importance of a regular psychological follow‐up for patients, but also of a psychological support for families. Helping the patients to overcome the difficulties at adolescence may improve their mental health in adulthood.